The femicide as a part of the culture of violence - Pavićević Olivera; Glomazić Hajdana; Ilijić Ljeposava (Temida, 2016)
In the paper femicide is analyzed as a gender-based violence whose origin is in feminicide. Feminicide is a term which designates social, cultural and ideological construction which survives in the continuity of institutional weakness. Gender-based violence appears as a mixture of institutionalized misogyny, patriarchate and abolition of women`s rights as human rights. The paper starts from the assumption that the basis of feminicide is in the continuity of the culture of violence and ideological matrices which promote adversarial discourse toward women, where amplified social and cultural tensions move to the sphere of gender-based violence. Femicide, as a visible and manifest violence, derives from the invisible institutional structure in which violence is continual, cyclical and reproductive. The subject of this paper is the attempt to get an insight into the invisible background of femicide as a form of violence rooted in feminicide. Its aim is contextualization of femicide into the existing structure of violence, and an analysis of some aspects of its social and cultural origin.